Diagnostic kit for early assessment of risk of adverse reactions to chemotherapy of taxanes - JING QIANG; GUO LIANG; SHI XIN; ZHOU CHENXI (2019)
The invention belongs to the field of genetic engineering and oncology, and discloses a diagnostic kit for early assessment of the risk of adverse reactions of chemotherapy of taxanes. The kit is usedfor predicting the risk of myelosuppression in a subject caused by chemotherapy drugs of taxanes. The kit comprises four pairs of SNPs locus genotype specific amplification primers and four specificextension primers, and targeted detection genes include a drug transporter gene SLC15A1, a drug metabolism gene UGT1A1, a nuclear receptor gene NR1I2 and a nuclear receptor gene HNF4alpha. The detection locus used in the kit is a susceptible SNPs for myelosuppression associated with the chemotherapy drugs of the taxanes. By detecting, the occurrence risk of taxane-related myelosuppression can be effectively evaluated, and the precise administration of the taxanes can be promoted. 本发明属于基因工程及肿瘤学领域，公开了一种早期评估紫杉烷类药物化疗不良反应风险的诊断试剂盒，是用于预测紫杉烷类化疗药物引起受试者发生骨髓抑制风险的诊断试剂盒，所述试剂盒包括四对SNPs位点基因型的特异性扩增引物与四条特异性延伸引物，针对的检测基因为药物转运体基因SLC15A1、药物